Drug Use and Misuse A Community Health Perspective - Bazan, Christy N.; Barnes, Brandi; Santens, Ryan; Verone, Emily (Open textbook library., 2022)
Drug Use and Misuse: A Community Health Perspective provides students with an introduction to the biological, psychological, and legal aspects of drug use and misuse through the lens of community health and discusses the impact of drug use and misuse on community health. The book contains eight distinct chapters addressing the background of drug use and misuse, including key terms, as well as an introduction to different categories of drugs including gateway drugs, opioids, and prescription drugs, and a conclusion that describes evidence-based prevention and treatment models. Originally developed for use in the popular undergraduate survey course “Drug Use and Abuse” taught at the University of Illinois Urbana-Champaign, the book is aimed at students learning about community health and the effects of drug use in a variety of contexts, such as survey courses for pharmacology, psychology, or public health.